2004
DOI: 10.1007/s00415-004-0327-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of subthalamic nucleus stimulation on parkinsonian dysarthria and speech intelligibility

Abstract: Subthalamic stimulation is known to improve tremor, akinesia and rigidity in Parkinson's disease. However, other signs such as hypophonia and swallowing disorders can be relatively resistant to this technique. The effect on dysarthria remains unclear. The aim of this study was to investigate the effects of implantation of electrode and stimulation of the subthalamic nucleus (STN) on parkinsonian dysarthria. Seven patients were prospectively included. Electrodes (Medtronic) were implanted in both STN. The elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
1
5

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 33 publications
2
65
1
5
Order By: Relevance
“…37,39,57,58 In order to understand these seemingly conflicting results, the different mechanisms illustrated in our case reports need to be considered: (1) respiratory, phonatory, and articulatory components of speech can be improved like other limb motor function (speech subcomponents are improved); (2) complex coordination of all anatomical substrates involved in speech might not be responsive to STN stimulation (intelligibility is not improved); and (3) current diffusion outside the target or target-related dyskinesias may lead to a worsening of speech intelligibility and seems to be a frequent fact (intelligibility can worsen). 36,39 In other words, item 18 of the UPDRS does not adequately evaluate the often complex speech changes that may result from L-dopa treatment or STN stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…37,39,57,58 In order to understand these seemingly conflicting results, the different mechanisms illustrated in our case reports need to be considered: (1) respiratory, phonatory, and articulatory components of speech can be improved like other limb motor function (speech subcomponents are improved); (2) complex coordination of all anatomical substrates involved in speech might not be responsive to STN stimulation (intelligibility is not improved); and (3) current diffusion outside the target or target-related dyskinesias may lead to a worsening of speech intelligibility and seems to be a frequent fact (intelligibility can worsen). 36,39 In other words, item 18 of the UPDRS does not adequately evaluate the often complex speech changes that may result from L-dopa treatment or STN stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…First, the UPDRS is insufficient to characterize the dysarthria of PD. Alternative perceptual scales 36,59,60 may be used to allow a more accurate description of the presenting dysarthria, including the examination of individual speech subsystems. 61,62 Second, self-evaluation of patients' speech must be taken into account, since the patient's perception of voice seems to reveal more details that can be heard by the clinician.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several studies have shown that clinically effective stimulation of the STN, with a significant improvement of the motor symptoms, may have an independent influence on speech. Along with substantially improved motor symptoms, some patients may obtain negative stimulation-induced effects on speech during STN DBS [10][11][12][13][14][15][16] . At other times, there may be no effects at all [17,18] , or sometimes positive effects on speech during clinically effective STN stimulation [19][20][21][22] .…”
Section: Speech and Movement During Dbsmentioning
confidence: 99%
“…Different approaches have been chosen to study biolinguistic effects of DBS, comprising the assessment of language under active versus inactive stimulation, under variation of DBS parameters and before versus after surgery (Bordini, Garg, Gallagher, Bell, & Garell, 2007;Carpenter et al, 1998;D'Alatri et al, 2008;Klostermann et al, 2008;Puetzer, Barry, & Moringlane, 2008;Rousseaux et al, 2004;Saint-Cyr, Trépanier, Kumar, Lozano, & Lang, 2000;Santens, De Letter, Van Borsel, De Reuck, & Caemaert, 2003;Toernqvist, Schalén, & Rehncrona, 2005;Tripoliti, Limousin, Tisch, Borrell, & Hariz, 2006;Tripoliti et al, 2008;Wang et al, 2006). Most of these studies were performed under clinical rather than neuroscientific aspects, the major concern being the safety of the therapeutic procedure (Ardouin et al, 1999;Dujardin, Defebvre, Krystkowiak, Blond, & Destee, 2001;Saint-Cyr & Albanese, 2006;Saint-Cyr et al, 2000).…”
Section: Effects Of Dbs On Language Functionsmentioning
confidence: 99%